Systematic biases in determining dust attenuation curves through galaxy SED fitting. Issue 1 (28th January 2022) - Qin, Jianbo; Zheng, Xian Zhong; Fang, Min; Pan, Zhizheng; Wuyts, Stijn; Shi, Yong; Peng, Yingjie; Gonzalez, Valentino; Bian, Fuyan; Huang, Jia-Sheng; Gu, Qiu-Sheng; Liu, Wenhao; et al.
ABSTRACT: While the slope of the dust attenuation curve (δ) is found to correlate with effective dust attenuation ( A V ) as obtained through spectral energy distribution (SED) fitting, it remains unknown how the fitting degeneracies shape this relation. We examine the degeneracy effects by fitting SEDs of a sample of local star-forming galaxies (SFGs) selected from the Galaxy And Mass Assembly survey, in conjunction with mock galaxy SEDs of known attenuation parameters. A well-designed declining starburst star formation history is adopted to generate model SED templates with intrinsic UV slope (β0 ) spanning over a reasonably wide range. The best-fitting β0 for our sample SFGs shows a wide coverage, dramatically differing from the limited range of β0 < −2.2 for a starburst of constant star formation. Our results show that strong degeneracies between β0, δ, and A V in the SED fitting induce systematic biases leading to a false A V –δ correlation. Our simulation tests reveal that this relationship can be well reproduced even when a flat A V –δ relation is taken to build the input model galaxy SEDs. The variations in best-fitting δ are dominated by the fitting errors. We show that assuming a starburst with constant star formation in SED fitting will result in a steeper attenuation curve, smaller degeneracy errors, and a stronger A V –δ relation. Our findings confirm that the A V –δ relation obtained through SED fitting is likely driven by the systematic biases induced by the fitting degeneracies between β0, δ, and A V .